Gramatičeskie aspekty semantiki pervogo lica - Kireeva, Elena Zakirovna (Slavistična revija, 2015)
The article focuses on the pragmatic aspects of first-person semantics, i.e., on functioning of linguistic expressions and reference correlation. The research is based on the premise that the author of an official document manifests him- or herself in the text, i.e., s/he per - sonifies an authority or its representative(s) rather than its executives-civil servants. The research material consists of official documents-statutory and regulatory acts from regional legislation.
Keywords: grammar; Pro-form; slovnica; slovnične kategorije; sporazumevanje; uradovalni jezik; zaimek